2002
DOI: 10.1177/0143034302234002
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Practices, Ethnicity, Socioeconomic Status and Academic Achievement in Adolescents

Abstract: This study was concerned with the relationship between parenting practices and academic achievement of high school students. A sample of 873 Asian Americans, 1449 Hispanics, 1176 African Americans and 8292 European Americans was selected from the first follow-up (1990) and second follow-up (1992) of the National Educational Longitudinal Study (NELS). Analysis of variance (ANOVA), hierarchical and stepwise multiple regressions were employed to determine the extent to which parenting practice predicts academic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 11 publications
6
51
1
1
Order By: Relevance
“…In contrast, there was no significant relationship between authoritarian parenting style and school achievement. The present finding is similar to the findings by Kim and Rohner (2002), Park andBauer (2002), andOlige (2008). Authoritarian parents tend to practice rigid and high level of monitoring.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, there was no significant relationship between authoritarian parenting style and school achievement. The present finding is similar to the findings by Kim and Rohner (2002), Park andBauer (2002), andOlige (2008). Authoritarian parents tend to practice rigid and high level of monitoring.…”
Section: Discussionsupporting
confidence: 93%
“…Adolescents who had parent with authoritative style were more successful in school. The results are consistent with Park and Bauer (2002), Attaway and Bry (2004), Gonzalez-DeHass et al, (2005), Slaten (2006), Roche et al (2007), Simons and Conger (2007) and Ling Pong et al (2009) which found that authoritative parenting style promote school achievement. Durkin (1995) highlighted three reasons for the association between authoritative parenting and high school achievement.…”
Section: Discussionsupporting
confidence: 86%
“…Students who had parent with authoritative style were more successful in school. The results are consistent with Park and Bauer (2002), Attaway and Bry (2004), which found that authoritative parenting style promote school achievement.…”
Section: Inter-correlations Between Predictor Variables and Academic supporting
confidence: 89%
“…Research based on Baumrind's model has yielded fairly consistent findings on the parenting behaviors that promote positive adjustment in children, particularly among middle-class, Caucasian families (Baumrind, 1989;Chao, 2001;Darling & Steinberg, 1993;Park & Bauer, 2002;Querido, Warner, & Eyberg, 2002). Authoritative parenting (characterized by emotional supportiveness, limit setting, and firm yet responsive disciplinary strategies) is consistently associated with positive educational, social, emotional, and cognitive developmental outcomes in children.…”
mentioning
confidence: 99%